Path Player Games Analysis and Applications - Schwarze, Silvia; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
A path player game is a new innovative type of game which considers network flow problems from the viewpoint of network owners. This strategy enables modeling real-world problems and has many practical applications. Key features: * Presents a rigorous exposition of the theoretical foundations of the concept of a path player game; * Suggests 18 practical open problems for future research in such areas as traffic planning, computation of equilibria, and optimization; * Examines potentials for games on polyhedra as well as integer versions of generalized Nash equilibria. Written clearly, with well-presented mathematics, this book is intended for graduate students, mathematicians, engineers, and computer scientists.
The path player Game -- Games on Polyhedra A Generalization -- The Line Planning Game: An Application -- Summary.
Keywords: MATHEMATICS; MATHEMATICAL OPTIMIZATION; OPERATIONS RESEARCH; ECONOMICS, MATHEMATICAL; MATHEMATICS; OPTIMIZATION; GAME THEORY/MATHEMATICAL METHODS; OPERATIONS RESEARCH, MATHEMATICAL PROGRAMMING